Contestation of Religious Authority: Institutional vs Cultural Islamic Power Struggles in Aceh's Dike Situek Ritual Sovereignty Conflict - Mugni, Abdul; Subakat, Rahayu; Sonko, Fatoumata (JURNAL INDO-ISLAMIKA, 2025)
This study analyzes religious-political contestation dynamics fueling social conflict in Aceh, Indonesia, through qualitative analysis of interactions between orthodox Dayah institutions and minority Dike Situek practitioners. Employing conflict theory with empirical data from interviews (n=32), participant observation, and document analysis, three critical mechanisms emerge: 1) Majority religious actors strategically stigmatize minority groups to consolidate political power; 2) State-endorsed fatwas institutionalize marginalization, transforming religious authority into socioeconomic capital; 3) Effective conflict resolution necessitates cultural mediation frameworks reconciling orthodox and cultural Islamic perspectives. The findings advance socio-religious conflict theory by demonstrating how state-religion alliances escalate majority-minority tensions, while proposing policy interventions for institutional accommodation of minority practices. Limitations include insufficient historical documentation of Dike Situek origins, highlighting the urgency of oral history preservation. Contributing to global discourse on post-conflict religious pluralism, the research advocates localized cultural approaches to mitigate politicized religious tensions in transitional societies..